Research on Multi-Stage Optimization of Impeller For Multi-stage Culvert Type Natural Gas Pressure Energy Power Generation Device - Yu, Kun; Zhang, Ran; Chen, Ying; Dai, Haowen (International Journal of Mechanical and Electrical Engineering, 2026)
Under the "dual carbon" framework, the pressure energy benefit of recovering natural gas pressure regulation loss is significant. This article proposes an optimized design for a multi-stage culvert impeller, featuring a relatively simple structure, small footprint, and low leakage risk, specifically tailored for existing pressure difference power generation technology. Through optimization of the number of stages and spacing, it is confirmed that the theoretical power of a three-stage impeller increases by 31.8% compared to a single-stage impeller under a spacing of twice the impeller radius, providing an efficient and low-leakage solution for small and medium-sized pressure energy recovery.